Short term stress: effects on cortisol and carotenoid spots in Arctic charr (Salvelinus alpinus L., 1758) - Backström, Tobias; Johansson, Kajsa; Brännäs, Eva; Nilsson, Jan; Magnhagen, Carin (NRC Research Press (a division of Canadian Science Publishing), 2016)
Earlier studies have shown that the carotenoid pigmentation in Arctic charr (Salvelinus alpinus L., 1758) is connected to stress responsiveness. These studies also suggested that the pigmentation is dynamic and can change quickly. Therefore, we wanted to investigate the effect of a short term stressor on the number of carotenoid spots before and after certain time intervals after the stressor. Individuals were exposed to a net restraint stressor for one minute and then assigned a recovery time of either 0, 1, 2, 8, or 24 hr. Photographs were taken before the stressor and after recovery time to count carotenoid spots and look at the relative changes over time. Behaviour during the stressor and cortisol levels after assigned recovery time were evaluated. We found that the change of spottiness, measured as the ratio of spots after and before the stressor, changed with recovery time on the right side but not the left side. Further, left side spots were correlated with struggling activity. Thus, carotenoid pigmentation seems to be lateralized, with more static spots on the left side connected to stress responsiveness, whereas spots on the right side seems to be more dynamic. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.